2006
DOI: 10.1080/14034940510032383
|View full text |Cite
|
Sign up to set email alerts
|

Fertility in Norwegian women: Results from a population-based health survey

Abstract: Fertility problems were quite common, and have increased in younger age groups, though seemingly fewer women remained childless past their reproductive age in the youngest age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
2
11
2
Order By: Relevance
“…Interestingly, higher levels of infertility were observed among women with higher levels of education, with the cultural level having been involved with the decision to become pregnant later. 29 These findings are different from the values found in a Portuguese epidemiological study that showed that the majority of infertile women have four or less years of education. 3 The observation that most of the infertile women (83%) did not smoke and that of those who smoke 45% consumed less than 10 cigarettes per day clearly indicates that women are aware of the pernicious effects of smoke.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, higher levels of infertility were observed among women with higher levels of education, with the cultural level having been involved with the decision to become pregnant later. 29 These findings are different from the values found in a Portuguese epidemiological study that showed that the majority of infertile women have four or less years of education. 3 The observation that most of the infertile women (83%) did not smoke and that of those who smoke 45% consumed less than 10 cigarettes per day clearly indicates that women are aware of the pernicious effects of smoke.…”
Section: Discussioncontrasting
confidence: 64%
“…The negative impact on fertility is the same reported to cigarette smoke. 24,29 This finding suggests that women need to find a recreational consumption that instead of smoking is being directed to alcohol consumption. These findings contrast with the values found in a Portuguese epidemiological study that indicated that the majority of infertile women do not consume alcoholic beverages.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, a similar trend in lifetime history of infertility was observed by Rostad et al in a population-based study in Norway. 38 Stratifying by whether a Veteran had ever become pregnant or fathered a pregnancy, this pattern was less apparent, in our analysis, among those who had never become pregnant or fathered a pregnancy with the highest prevalence of self-reported history of infertility observed in those 35-44 years old (data not shown).…”
Section: Infertility Among Men and Women Veterans 177contrasting
confidence: 62%
“…A population-based study of Scotland found a somewhat higher risk of infertility in those with both high and low levels of education, but no relationship with social deprivation,[6] while a Norwegian study found higher levels of involuntary childlessness with higher education, and reduced levels among those were manual workers. [7] However, a study of the Danish population found no difference in lifetime prevalence of infertility by social class[3]. …”
Section: Introductionmentioning
confidence: 99%